EP.FRI.116 Bleeping Etiquettes. (28th October 2021) - Sandhya, Anu; Oyewole, Bankole; Ng, Vivian; Cheng, Amanda; Ghani, Anum; Mangat, Shannon
Abstract: Introduction: Bleeps are a vestige of decades old technology common place in NHS Trusts. No formal guidelines exist to regulate the use of the bleep leading to user frustration on both ends of the system. Many junior doctors reported a high number of inappropriate and disruptive bleeps. This quality improvement project aimed to formulate a guide for the use of the bleep system. Methods: Formal interviews were conducted among clinical and non-clinical staff as to the expectations in the use of the bleeping system. A list of bleeping etiquettes was created following formal interview and formed the basis of a Trust survey to formulate a Bleeping protocol. Results: The following bleeping etiquettes were agreed upon; Bleep once and give at least 10 to 15 minutes before bleeping back After bleeping stay by the phone for about 3 to 5 minutes Only bleep from one phone rather than multiple bleeps from multiple phones from the same department Fast bleep for very urgent or emergencies requirements MET calls as per protocol for deteriorating patients not multiple bleeps Escalate to the next level if no response after bleeping 3 times within 30 minutes for urgent cases Get all necessary jobs/referrals/queries/information together before bleeping. Avoid bleeping during ward rounds, teaching sessions or lunch breaks for non-urgent cases Conclusion: A formalized protocol for bleeping can lead to a more effective and stress-free bleeping system.